Religion in the Digital Age: An Irreversible Process - Bingaman, Kirk A. (Religions, 2023)
Digital technology is fundamentally changing what it means to be human, in particular what it means to be a religious or spiritual human being, as it becomes an “irreversible” process. Indeed, the process is having a seismic impact on the religious and spiritual lives of “digital natives”, who have never known a world without the Internet. This paper will seek to determine, by way of the Digital Theology method put forward by Sutinen and Cooper, if the religious-disaffiliation trend among younger populations is connected to the digitalization of society, either causally or correlationally, and what, if anything, religious leaders and faith communities can do about it. Research on the effects of high social media usage will be given special attention, in order to highlight the double-edged nature of digital technology.